Medicine Information Monitoring System In Web-Based Medical Clinics: Medicine Information Monitoring System In Web-Based Medical Clinics - Fierzha Anugrah Putra; Abdul Rohim Gumilar (Institute of Computer Science (IOCS), 2020)
Bunda Medika Clinic is a business entity that serves general medicine (general practitioners and dentists), midwifery services, and BPJS services in childbirth. Along with the variety of services at the BundaMedika Clinic, the supply of medicines is increasing. With the variety of services, so too many types and quantities of drugs. Currently the process of selling transactions, checking, and recording of drugs at the clinic is still done conventionally using a written form. In order to facilitate officers in conducting sales transactions, checking, and inputting drugs, the authors make a drug monitoring information system at the BundaMedika Clinic. This monitoring information system can display drug stocks so that they can assist officers in checking the availability of drugs, conduct drug sales transactions, display incoming stock reports containing notifications about what drugs have just been added. And display outgoing stock reports derived from drug sales transactions.